An Early Morning Sputum Sample Is Necessary for the Diagnosis of Pulmonary Tuberculosis, Even with More Sensitive Techniques: A Prospective Cohort Study among Adolescent TB-Suspects in Uganda. (4th December 2012) - Ssengooba, Willy; Kateete, David P.; Wajja, Anne; Bugumirwa, Eric; Mboowa, Gerald; Namaganda, Carolyn; Nakayita, Germine; Nassolo, Maria; Mumbowa, Francis; Asiimwe, Benon B.; Waako, James; Verver, Suzanne; et al.
Abstract : The World Health Organization (WHO) recommends collection of two sputum samples for tuberculosis (TB) diagnosis, with at least one being an early morning (EM) using smear microscopy. It remains unclear whether this is necessary even when sputum culture is employed. Here, we determined the diagnostic yield from spot and the incremental yield from the EM sputum sample cultures among TB-suspected adolescents from rural Uganda. Sputum samples (both spot and early-morning) from 1862 adolescents were cultured by the Lowenstein-Jensen (LJ) and Mycobacterium Growth Indicator Tube (MGIT) methods. For spot samples, the diagnostic yields for TB were 19.0% and 57.1% with LJ and MGIT, respectively, whereas the incremental yields (not totals) of the early-morning sample were 9.5% and 42.9% (P < 0.001 ) with LJ and MGIT, respectively. Among TB-suspected adolescents in rural Uganda, the EM sputum culture has a high incremental diagnostic yield. Therefore, EM sputum in addition to spot sample culture is necessary for improved TB case detection.